Biochemical Pathway of Flavonoids Biosynthesis - S. Gejalakshmi; Harikrisnan. N; Aswin. C (Chemistry and Biochemistry: Research Progress Vol. 6, 2025)
Flavonoids are phytochemical compounds present in many plants, fruits, vegetables, and leaves, with potential applications in medicinal chemistry. These compounds are polyphenolic due to the presence of different phenol groups. Such compounds contribute to various functions in plants, including the colour of flowers or even foliage that protects against UV rays; these flavonoids might even protect the plant itself from insects. This study described how these flavonoids are biosynthesised. These compounds come from an amino acid called phenylalanine. Flavonoids are biosynthesised through the phenylpropanoid pathway, which has a series of steps. In the first step, an enzyme called phenylalanine ammonia-lyase (PAL) converts phenylalanine into cinnamic acid. Then two more enzymes, cinnamate-4-hydroxylase (C4H) & 4-coumarate-CoA ligase (4CL), combine to make p-coumaroyl-CoA. The next step is that the chalcone synthase (CHS) accepts p-coumaroyl-CoA, condenses it with malonyl-CoA, and then chalcones are formed. Chalcone isomerase (CHI) comes afterwards and catalyses chalcone into naringenin. But then the hydroxylation and glycosylation add other cool tweaks that help in the formation of varied flavonoids like quercetin, kaempferol, and anthocyanins. The whole process is tightly regulated by genetic and environmental factors, which are highly important for how plants grow, and could even be important for human health.